Type 2B von Willebrand Disease: A Matter of Plasma Plus Platelet Abnormality - Castaman, Giancarlo; Federici, Augusto B. (Seminars in Thrombosis and Hemostasis, 2016)
Type 2B von Willebrand disease (VWD2B) is a rare, autosomal-dominant inherited bleeding disorder, characterized by an enhanced ristocetin-induced platelet aggregation in platelet-rich plasma and often with variable degree of thrombocytopenia and loss of high-molecular-weight multimers von Willebrand factor (VWF). All these phenomena are caused by a mutant VWF, normally synthesized and assembled by endothelial cells, but with heightened affinity binding to the platelet receptor glycoprotein Ib-α (GpIb-α). When this abnormal VWF is released into the circulation and under specific clinical circumstances, in vivo platelet clumping is observed. Mutations, invariably clustered in exon 28 of the VWF gene encoding for the VWF A1 domain involved in VWF binding to GpIb-α, are responsible for VWD2B phenotype. Clinical and laboratory phenotype appears strongly related to the type of VWF-causative mutations. However, recent evidences suggest that a true platelet defect is also present in this type, with several morphological and functional abnormalities being detected in a subset of VWD2B patients.
Keywords: von Willebrand disease; type 2B; thrombocytopenia; inherited bleeding disorders; platelets; platelet function disorders